PENGARUH KOMPRES HANGAT PADA PAYUDARA TERHADAP PRODUKSI ASI PADA IBU NIFAS DI KLINIK GRAND RAYA HUSADA PANDANARUM - Wahyuwihayanti, Riris; Ilmiah, Widia Shofa; Wijayanti, Tut Rayani Aksohini (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Mother's breast milk production is one of the factors so that toddlers' breast milk needs can be met. Lack of breastfeeding for children aged 0-3 years will have an impact on the child's cognitive development and physical growth. Warm compresses on the breasts during breastfeeding will increase the flow of breast milk from the breast-producing glands. Other benefits of warm compresses on the breasts include stimulating the let down reflex, preventing dams in the breasts, improving blood circulation in the breast area, and reducing muscle pain caused by ischemia. The purpose of this study was to analyze the effect of warm compresses on the breasts on breast milk production in postpartum mothers at the Grand Raya Husada Pandanarum Clinic. The research method used was pre-experimental with a one group pretest posttest design. Sampling used accidental sampling, the number of samples is 30 respondents. The research instrument used a questionnaire. The results showed that the average breast milk production before warm breast compresses (Pre-test) was 18.5 cc with a standard deviation of 11.74 cc. After applying a warm breast compress (post test), the average breast milk production was 40.50 cc with a standard deviation of 20.04 cc. It can be seen that the mean difference between the pre-test and post-test is 22 cc with a standard deviation of 8.2 cc. The statistical test results also obtained a p value = 0.000, so it can be concluded that there is a significant influence between breast milk production before and after warm breast compresses. To help smooth breast milk production for post-partum mothers, health workers can provide warm breast compress intervention to stimulate the hormone oxytocin which can facilitate post-partum mothers' breast milk production.